Intra-household impact of improved dual-purpose cowpea on women in northern Nigeria - Tipilda, A; Alene, A.; Manyong, Victor M.; Singh, B. (2005)
This study explores the intra-household impact of transfer of improved dualpurpose cowpea from a gender perspective. Increased productivity by IDPC, has increased food, fodder and income availability. The impact of which is linked to the income it has placed in the women’s hands. Surplus income has been found to be extremely important in providing food and nutritional benefits to the home, particularly during periods of risk. Most importantly, income generated through the adoption of IDPC has entered a largely female domain, where transfers of gifts and income reserves were passed on from generation to generation. Having meaningful impact towards the social and economic development for the women. However, the technology has strengthened the separation of working spheres between men and women, with the associated seclusion of wives. Future IITA technologies, should attempt from the onset, to use alternatives, existing within the local rubric, to target women, with the aim of expanding their participation and contribution to agriculture with the associated benefits to their families.